Quantum theory of ultrafast magnetism - Simoni, Jacopo (Trinity College (Dublin, Ireland). School of Physics, 2017)
The ultrafast demagnetization of ferromagnetic Fe based clusters, bulk transition metals and anti-ferromagnets initiated by an optical excitation is studied by making use of the time-dependent spin density functional theory. In particular after a brief introduction and the exposition of some preliminary results in Chapter 1, we proceed in Chapter 2 by describing the state of the art of the theoretical basis of the ultrafast demagnetization process. In Chapter 3 we look in more details at the time dependent spin density functional theory method that will be used in the successive chapters to simulate the ultrafast spin dynamics in the first few tens of femtoseconds. In Chapter 4 we investigate the role played by the spin-orbit interaction on the onset of the demagnetization process, it is found that the demagnetization occurs locally, in the vicinity of the atomic sites, and the initial rate of spin loss is proportional to the square of the ionic spin orbit coupling strength. A simplified quantum spin model comprising the spin-orbit interaction and an external time-dependent magnetic field is found to be the minimal model able to reproduce the ab initio results. In Chapter 5 the spin continuity equation is reformulated in such a way that the torque due to the spin-current divergence may be expressed in terms of a kinetic field that is formally equivalent to an out-of-equilibrium spin-spin interaction. This field is identified as one of the main sources of the local out-of equilibrium spin dynamics and plays a major role in the demagnetization process. Such demagnetization is particularly strong in “hot spots” where the kinetic torque is maximized. In the final Chapter we analyze instead the ultrafast dynamics of the orbital momentum studying more in details its effects on the spin dynamics of the Fee cluster. We find that the rate of demagnetization is strongly dependent on the direction of polarization of the applied electric field and we develop, in order to explain this effect, a model based on the interplay of the ultrafast orbital current and the electric field with the spin orbit coupling.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2017